COMPETITIVENESS OF PENSION FUNDS IN INDIA - B.V, Pushpa (The journal of contemporary issues in business and government, 2021)
There are two groups of firms or companies in a market to influence the price of their products, namely, the price markers and price takers. The extent of market power and market concentration of these companies determine to which group they fall under. These issues needs a thorough discussion especially at the present time when Indian economy has shown a phenomenal trend because of changes in government policies as well as changing trends in lifestyle and saving pattern of people. Change in market concentration leads to change in market power. As concentration rate increases, level of competition decreases and vice versa. The issue is how to measure and interpret meaningfully the level or extent of market competition of the companies operating in pension market in India. Concentration Ratio (CR) and the Herfindahl-Hirschman Index (HHI) are two indicators. The present paper studies intensity of competition in pension market using the Herfindahl-Hirschman Index (HHI). The study provides inputs to the government & organizations to bring in further competitive strategies to benefit organisations. The H indices indicate near perfect behaviour of ICICI, Kotak, Reliance, HDFC & Birla Sun Life pension funds. SBI & UTI pension funds are monopolistic & exhibit monopoly power in their earnings. Given the present position, Pension Market Players (PMP) have a huge opportunity in Indian scenario as almost 94% of the total working population are not covered so far.